Waddenland outstanding : history, landscape and cultural heritage of the Wadden Sea region - Egberts, Linde; Schroor, Meindert (2018)
The Wadden Sea Region is comprised of the embanked coastal marshes and islands in the Wadden Sea near Denmark, Germany, and the Netherlands, and this area retains an exceptional common history in all its aspects: archaeologically, economically, socially, and culturally. Its settlement history of more than two thousand years is unrivalled and still mirrored in the landscape and even though it has never constituted a political unity, it still shares a landscape and cultural heritage. For example, the approaches to water management and associated societal organisation developed in the region during the last millennium have set significant world standards, values which were recognised by UNESCO in inscribing the Wadden Sea on its World Heritage List. This book encompasses the contributions presented at the scientific symposium of prominent scientists who gathered in 2016 in Husum, Germany, a landmark event in sharing knowledge on the common history, landscape, cultural heritage of the Wadden Sea Region.